Learning with Digital Tools vs. Learning Through Digital Tools in Physical Education: Impacts on Student Perceptions - André Klostermann; Till Etterlin (Current Issues in Sport Science)
Introduction Digital technologies are increasingly integrated into physical education (PE), primarily as tools for supporting skill acquisition (Jastrow et al., 2022). However, digital technologies hold additional educational potential by fostering digital competencies, aligning with the concept of an educating PE (“erziehender Sportunterricht”) (e.g., Wibowo et al., 2023). A key factor for adopting technology-based learning has been identified as perceived ease of use (PEU) and perceived usefulness (PU) (Granić & Marangunić, 2019). Therefore, this study investigates the effects of two intervention types on PEU and PU: (1) learning with digital tools (LWD), aimed at skill acquisition, and (2) learning with and through digital tools (LWTD), targeting skill acquisition and digital competency development. We hypothesized that LWTD would result in higher PEU and PU post-intervention.